CLINICAL COURSE OF PRIMARY HYPERPARATHYROIDISM IN POSTMENOPAUSAL WOMEN - Pardayeva Umida Yaxshimurodovna; Yangiboyeva Solihabegim Olimjonovna; Quvatova Madina Boqiyevna; Negmatova Gulzoda Shuhratovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Primary hyperparathyroidism (PHPT) is a common endocrine disorder and the leading cause of hypercalcaemia in the outpatient setting. The condition occurs predominantly in postmenopausal women and is often identified incidentally during routine biochemical testing, as many patients remain asymptomatic or experience only subtle, nonspecific symptoms for prolonged periods. PHPT is characterised by excessive secretion of parathyroid hormone (PTH), most frequently arising from a single parathyroid adenoma. The effects of PHPT on the skeleton are particularly important in postmenopausal women. Estrogen deficiency, which already accelerates bone loss after menopause, may act synergistically with PTH-induced bone resorption, further compromising bone strength and increasing the risk of osteoporosis and fragility fractures, especially at the spine, distal radius, and hip. In addition, vitamin D status plays a significant role in determining disease severity. Vitamin D deficiency is common among patients with PHPT and may aggravate skeletal involvement, influence biochemical abnormalities, and affect postoperative recovery after parathyroidectomy. This review discusses the current understanding of PHPT in postmenopausal women, focusing on its epidemiology, underlying mechanisms, impact on bone health, and available treatment options. Particular emphasis is placed on distinguishing the skeletal effects of menopause from those directly attributable to PHPT, as well as on the role of surgical and medical management in reducing fracture risk and improving long-term outcomes.